(untitled) - Blackwell, Roger (Hoboken, N.J., 2004)
Brands That Rock highlights strategies for developing deep connections between brands and people that are used by many of today’s biggest and longest-lived rock groups, including: Building brand loyalty one fan group at a time, Staying fresh in the marketplace while staying true to your core strength, Evolving at a rate that doesn’t alienate current customers, Focusing on the entire brand experience, and Exuding energy and passion to command respect and grab attention
Keywords: Music trade,Musicians,popular music; marketing,economic aspects